Tingkat Kepatuhan Pasien Diabetes Melitus Tipe II terhadap Penggunaan Obat Antidiabetes di Puskesmas Yosowilangun Kabupaten Lumajang - Yahya Wahyu Muhaymin; Andini Andini (LPPMKI - AKAFARMA AKFAR PIM, 2023)
Type II Diabetes Mellitus is a chronic condition that occurs when there is an increase in glucose levels in the blood caused by the body's inability to produce or use insulin effectively, resulting in sustained complications if not balanced with medication adherence. This study aims to determine the level of adherence of Type II Diabetes Mellitus patients to antidiabetic medication use in Yosowilangun Public Health Center in Lumajang Regency. This research method is a descriptive study using the MMAS-8 questionnaire as a data collection instrument with a total of 60 respondents. The results of this study showed that the average score of 60 respondents was 5.05, which indicates low adherence. From the results of the study, it can be concluded that the level of adherence of Type II Diabetes Mellitus patients in Yosowilangun Community Health Center, Lumajang Regency, falls under the low adherence category.